Characterization of antigen-specific CD8+ memory T cell subsets in peripheral blood of patients with multiple sclerosis - Liu, Pen-Ju; Yang, Ting-Ting; Fan, Ze-Xin; Yuan, Guo-Bin; Ma, Lin; Wang, Ze-Yi; Lu, Jian-Feng; Yuan, Bo-Yi; Zou, Wen-Long; Zhang, Xing-Hu; Liu, Guang-Zhi (Frontiers in Immunology, 2023)
Background: Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Increasing evidence indicating the importance of CD8+ T cells in autoimmune attack against CNS myelin and axon in MS. Previous studies have reported that myelin-reactive T cells display a memory phenotype in MS patients. However, there is limited evidence regarding the role of CD8+ memory T cell subsets in MS. This study aimed to explore potential antigen-specific memory T cell-related biomarkers and their association with disease activity. Methods: The myelin oligodendrocyte glycoprotein (MOG)-specific CD8+ memory T cell subsets as well as their related cytokines (perforin, granzyme B, interferon (IFN-γ)) and negative co-stimulatory molecules (programmed cell death protein 1 (PD-1), T- cell Ig and mucin domain 3 (Tim-3)) were analyzed by a flow cytometry and real-time PCR in peripheral blood of patients with relapsing-remitting MS. Results: We found that MS patients had elevated frequency of MOG-specific CD8+ T cells, MOG-specific central memory T cells (TCM), MOG-specific CD8+ effector memory T cells (TEM), and MOG-specific CD8+ terminally differentiated cells (TEMRA); elevated granzyme B expression on MOG-specific CD8+ TCM; and, on MOG-specific CD8+ TEM, elevated granzyme B and reduced PD-1 expression. In MS patients, The Expanded Disability Status Scale (EDSS) score was correlated with the frequency of MOG-specific CD8+ TCM, granzyme B expression in CD8+ TCM, and granzyme B and perforin expression on CD8+ TEM, but with reduced PD-1 expression on CD8+ TEM. Conclusion: The dysregulation of antigen-specific CD8+ memory T cell subsets, as well as the expression of their related cytokines and negative co-stimulatory molecules, may reflect a persistent chronic inflammatory response that may have been induced during early stages of the disease. Our findings strongly suggest positive regulatory roles for memory T cell populations in MS pathogenesis, probably via molecular mimicry to trigger or promote abnormal peripheral immune responses. Furthermore, downregulated PD-1 expression may stimulate a positive feedback effect, promoting MS-related inflammatory responses via the interaction of PD-1 ligands. Therefore, these parameters are potential serological biomarkers for the prediction of disease development in MS.